Politieke geschriften Opstand en Religievrede - Coornhert, D.V (Bibliotheca Dissidentium Neerlandicorum|Amsterdamse Gouden Eeuw Reeks, 2009)
In Root of the Dutch Wars and Other Political Writings, Coornhert provides his views on the political situation at that time in a profound manner. The political situation is according to Coornhert not only hopeless, but the liberation struggle appears to be meaningless when new acts of injustice are not punished. This book is a dialogue in which Coornhert further launches his criticisms and convictions. His work is a plea for tolerance, written with great sense of urgency at a crucial moment of our national history. The Bibliotheca Dissidentium Neerlandicorum publishes works on the non-coformist history of the Netherlands (religious, philosophical and artistic) of approximately 1350 until the present day. These works of various non-conformist authors are published by Amsterdam University Press, under the Coornhert Stichting imprint.